PEMBELAJARAN TEMATIK INTEGRATIF IPA DAN IPS DI MADRASAH IBTIDAIYAH PADA KURIKULUM 2013 - Novianti Muspiroh (Al Ibtida: Jurnal Pendidikan Guru MI, 2015)
Natural science and social science are integrated into the 2013 curriculum based on the themes in all subjects of Madrasah Ibtidaiyah (MI) (Islamic Primary School). The integration is done in two ways, namely the integration of attitudes, skills and knowledge in the learning process and the related basic concepts. Themes related to the meaning of the basic concepts, so students do not learn them partially. This approach is appropriate for MI students because of the psychological point of view; they have not been able to think abstractly to understand content of a separate subject. Thereby, the classroom atmosphere are comfortable and fun, students can learn to solve social problems and mutual respect, they get opportunities as possible to learn better, get the information quickly, apply materials directly in the context of daily life, and apply the principle of mastery learning.Â Keywords: Tematik, IPA, IPS, Madrasah Ibtidaiyah